Preparation of a limited compliance soft particle and its use as a pickering particle

CN118476605BActive Publication Date: 2026-10-23JIANGNAN UNIV +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202310108118.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-02-13
Publication Date
2026-10-23
Estimated Expiration
2043-02-13

AI Technical Summary

Technical Problem

[0006]综上,现有的皮克林粒子存在制备所得的乳液长期稳定性较差的问题

Benefits of technology

本发明基于绿色物理改性技术制备了高压均质化功能材料——具备有限顺应性的皮克林粒子,并利用具备有限顺应性的软粒子作为性能优异的界面稳定粒子(皮克林粒子)进行应用,从而制得乳液、泡沫、乳液凝胶和高内相乳液凝胶等材料,这些材料还可以应用于食品(如蛋黄酱和沙拉酱等)、保健品、化妆品、个人护理用品、洗涤剂、制药和医疗等各个领域的产品创制。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118476605B_ABST
    Figure CN118476605B_ABST
Patent Text Reader

Abstract

The application discloses a preparation method of limited-compliance soft particles and application of the limited-compliance soft particles as Pickering particles, and belongs to the field of new materials. The application utilizes commercial bulk food raw materials, and induces natural nanogel particles to plastically deform based on a very simple, fast and environment-friendly green industrial technology, namely, homogenization technology. Therefore, natural casein micelle nanogel particles with layered assembly structure change in size, morphology and internal architecture, realize regulation of particle softness and heterogenization of gel internal structure, and have advantages of hard particles and soft particles, and become excellent Pickering particles with limited compliance. The limited-compliance soft particles have good application prospects in various fields such as food, health products, cosmetics, personal care products, detergents, pharmaceuticals and medical treatment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a method for preparing finitely compliant soft particles and their application as Pickering particles, belonging to the field of new materials. Background Technology

[0002] Emulsions have wide applications in various fields such as food, health products, cosmetics, personal care products, detergents, pharmaceuticals, and medicine. Emulsifiers are substances that enable a mixture of two or more immiscible components to form a stable emulsion. Small-molecule surfactants, as emulsifiers, have drawbacks such as high dosage, significant side effects, environmental pollution, and high cost. Most natural macromolecules are highly hydrophilic and have poor emulsifying properties, making the prepared emulsions prone to phase inversion and exhibiting low stability.

[0003] Currently, emulsion stabilizers are no longer limited to small or large amphiphilic compounds. Solid particles have also been reported to possess interfacial activity, stabilizing emulsion droplets by providing a physical barrier to prevent aggregation; such emulsions are called Pickering emulsions. Early research on Pickering emulsions was mainly limited to inorganic particles, such as metal salts, clay particles, and silica particles, which are common inorganic Pickering stabilizers. Polymer colloidal particles have also been extensively studied in the past few decades, such as polystyrene (PS) and polymethyl methacrylate (PMMA) particles. These solid particle stabilizers are considered "hard particles," possessing high elastic modulus and being resistant to deformation. To obtain better emulsion stability or to endow the particles with more functions, certain physical or chemical methods are usually used to modify the Pickering particles, but surface modification is generally quite difficult. The reasons are twofold. First, when using small-molecule modified Pickering particles, the degree of surface modification is difficult to measure and control accurately without specialized equipment. Second, the preparation of small-molecule modified Pickering particles is often very complex, including unavoidable purification steps to remove unadsorbed molecules or the need to covalently bond small molecules to the particle surface through chemical reactions. These steps are difficult to implement, and some purification or reaction reagents are harmful to the human body. On the other hand, when using macromolecule modified Pickering particles, although there are many chemical modification methods, such as glycosylation and phosphorylation, and physical methods such as heat treatment, high-voltage pulsed electric fields, and ultrasonic treatment, these chemical or physical treatment methods themselves, as well as the step of fixing macromolecules to the surface of solid materials, will result in the macromolecules on the surface of the modified Pickering particles having a structure and conformation that is not completely identical to the free macromolecules before modification. Changes in the structure and conformation of macromolecules will simultaneously alter their physicochemical properties. Therefore, the effect of macromolecule modified Pickering particles is difficult to predict, and the degree of improvement may not be significant. In summary, obtaining high-performance Pickering hard particle materials is not easy, and most modification methods are not easily applicable to large-scale industrial production, making it difficult to commercialize these modified Pickering hard particle materials. Furthermore, food-grade Pickering particles suitable for use in food and health products are even more limited and harder to obtain.

[0004] Recent research has focused more on particles composed of soft matter. Unlike hard particles, soft particles can be designed into more diverse and interesting materials, such as responsive materials, with virtually limitless potential applications across various fields. Soft, deformable particles can spontaneously adsorb onto interfaces and form continuous viscoelastic interfacial layers, providing a degree of kinetic stability against Ostwald ripening. For example, nanogels are soft particles composed of internally cross-linked polymer networks, and their interfacial properties largely depend on their cross-linking density. Based on differences in the cross-linking density of the internal network, they can be classified into "uniformly cross-linked gels" and "non-uniformly cross-linked gels" (with an internal radial cross-linking density gradient). Completely soft particles, due to their high compliance, undergo radial compression and deformation at the interface, which may weaken their ability to resist Ostwald ripening of emulsions, thus hindering the preparation of long-term stable emulsions. In contrast, non-uniformly cross-linked gel particles (where the cross-linking density varies regionally within the particle) combine the advantages of both hard and soft particles (i.e., regions with higher cross-linking density resemble hard particles, while regions with lower cross-linking density resemble soft particles), while exhibiting spontaneous adsorption and limited compliance (the stiffness / softness of the particles can be adjusted). Since interfacial adsorption does not present a significant energy barrier, it is beneficial for improving foaming ability and emulsifying activity; furthermore, limited compliance can resist Ostwald curing, thus achieving long-lasting stability. However, designing and manufacturing a non-uniformly cross-linked particle that combines the advantages of both hard and soft particles, making it a soft particle with limited compliance, is extremely difficult. First, the non-uniform cross-linking chemical reaction is difficult to achieve and control. Second, the design of non-uniformly cross-linked particles requires comprehensive consideration of the characteristic lengths of soft particles, from global size, molecular weight, and elastic modulus to determining the length of the internal structure, such as core-shell thickness, mesh size, and local elastic modulus. Such a sophisticated design is theoretically difficult, and practically even more challenging.

[0005] Milk is a natural biological fluid that has evolved over time, capable of binding more calcium and inorganic phosphorus without causing pathological calcification of the mammary glands. To prevent calcium phosphate precipitation, calcium-sensitive casein (α-casein)... s1 -、α s2 α- and β-casein immobilize amorphous calcium phosphate nanoclusters, forming a complex hierarchical assembly called casein micelles (CM). Highly hydrated CMs are porous structures with numerous water-filled cavities and channels, stabilized by hairy κ-casein in the surface region. The interior of the CM is composed of various casein components (α- and β-casein). s1 -、α s2The matrix consists of β- and β-casein, with calcium phosphate nanoclusters acting as anchors for dispersion. CM's "sponge model" divides micelles into soft and hard regions, and the network constructed by protein-protein interactions generates large-scale protein inhomogeneities.

[0006] In summary, existing Pickering particles suffer from poor long-term stability of the resulting emulsions. Currently, the preparation of high-performance Pickering particles (such as surface-modified Pickering particles and soft particles with limited compliance, combining the advantages of both hard and soft particles) faces challenges in design and complex preparation procedures; most technologies remain at the laboratory stage, and reproducibility needs improvement; in particular, there is a very limited number of preparation technologies with prospects for industrial-scale production. Furthermore, although food-grade Pickering particles have broader application prospects and are crucial for stabilizing food emulsions and food foams, as well as for developing edible devices dominated by reconfigurable interfaces, constructing high-quality, edible Pickering particles remains a very challenging research area at this stage. Summary of the Invention

[0007] To address the aforementioned issues, this invention utilizes commercially available bulk food ingredients (milk protein concentrates rich in CM, casein micelle powder, and other milk protein ingredients) and, based on a very simple, rapid, and environmentally friendly green industrial technology—homogenization technology—to induce plastic deformation in natural casein micelle nanoparticles. This results in changes in the size, morphology, and internal structure of the naturally casein micelle nanoparticles, which possess a layered assembly structure. This allows for the regulation of particle softness and heterogeneity of the gel's internal structure, achieving the advantages of both hard and soft particles, resulting in high-performance Pickering particles with limited compliance.

[0008] This invention provides a method for preparing Pickering particles with limited compliance using milk protein. The Pickering particles with limited compliance refer to particles whose stiffness can vary. Typically, soft particles undergo a certain degree of deformation under stress. Completely soft particles possess high compliance (compliance refers to the ease with which an elastomer deforms under external force, which can be understood as softness). The Pickering particles prepared by this invention combine the advantages of both hard and soft particles, exhibiting both spontaneous adsorption and limited compliance (a certain degree of softness, meaning such particles will not completely collapse during interfacial adsorption). The method utilizes homogenization technology to treat a milk protein dispersion to obtain Pickering particles that influence fluid interfacial interactions.

[0009] In one embodiment of the present invention, the milk protein source includes, but is not limited to, cow milk, buffalo milk, goat milk, sheep milk, dromedary camel milk, Bactrian camel milk, donkey milk, and roe deer milk, and can be liquid milk or milk protein powder.

[0010] In one embodiment of the present invention, the milk protein may be liquid milk or milk protein powder.

[0011] In one embodiment of the present invention, the milk protein may be fresh or aged, including but not limited to casein micelle powder, milk protein concentrate, skim milk powder, low-fat milk powder, or whole milk powder. Aging refers to the storage of freshly prepared milk protein powder at room temperature for more than 6 months.

[0012] In one embodiment of the present invention, the milk protein dispersion may be a dispersion of fresh or aged milk protein concentrate, casein micelles, skim milk powder, low-fat milk powder, or whole milk powder.

[0013] In one embodiment of the present invention, the milk protein dispersion is an aqueous solution of milk protein, and the mass fraction of MPC relative to water is 0.1-15% w / w, preferably 1-12% w / w.

[0014] In one embodiment of the present invention, the homogenization process for treating the milk protein dispersion involves first stirring the milk protein dispersion at 200-800 rpm for 2 hours at 20-50°C, then continuing to stir at 200-800 rpm for 10-12 hours at 10-15°C, followed by preheating at 50-70°C for 10-30 minutes, and finally homogenization. Preheating the protein dispersion before homogenization significantly improves a key challenge in the industrial production of homogenization processes. Specifically, the homogenization process can cause localized temperature increases in samples, leading to inconsistent batch stability in heat-sensitive samples after homogenization and subsequent processing steps. This is a significant challenge in milk protein processing. The present invention, through experimental exploration, has established the importance and necessity of the preheating process, ensuring batch-to-batch stability.

[0015] In one embodiment of the present invention, the homogenization process is carried out at a pressure of 10–200 MPa, and the homogenization is performed 2–8 times. Preferably, the homogenization pressure is 30–150 MPa, and the homogenization is performed 3–6 times.

[0016] In one embodiment of the present invention, the method includes the following steps: Aged protein concentrate (MPC) was dispersed in ultrapure water and stirred at 600 rpm for 2 h at room temperature, followed by stirring at 600 rpm for 10 h at 15 °C. The MPC concentration after full hydration was 50 g·L⁻¹. -1 (5% w / w) The dispersion was first preheated to 50°C and then subjected to HPH or HPM treatment at homogenization pressures of 30, 60, 90, 120 and 150 MPa, and homogenized 3 times.

[0017] The present invention provides Pickering particles with limited compliance obtained by the above method.

[0018] This invention provides applications of the aforementioned limited compliance Pickering particles, such as encapsulating and delivering bioactive substances, gelling liquid oils, and helping to solve the antioxidant problems of oils, in the preparation of materials such as emulsions, foams, emulsion gels, and high internal phase emulsion gels. It also includes further applications of these materials in the manufacture of food (such as mayonnaise and salad dressing), health products, biomedicine, and daily chemical products, which helps to create advanced materials with structural hierarchy and complex interface functions.

[0019] In one embodiment of the present invention, when preparing the emulsion, the amount of Pickering particles with limited compliance relative to the aqueous phase is 1 to 12% w / w; preferably 1 to 6% w / w.

[0020] In one embodiment of the present invention, when preparing the emulsion, the volume ratio of the aqueous phase to the oil phase of the emulsion is 19:1 to 13:37; preferably 4:1.

[0021] This invention provides a method for preparing high internal phase emulsion gels using Pickering particles with limited compliance, wherein the high internal phase emulsion gel is obtained by high-speed shear dispersion using an MPC solution as the aqueous phase and conjugated linoleic acid (CLA) as the oil phase. Hyaluronic acid and / or hyaluronic acid salts are also added to the aqueous phase.

[0022] In one embodiment of the present invention, when preparing a high internal phase emulsion gel, the volume ratio of the aqueous phase to the oil phase of the high internal phase emulsion gel is 1:3 to 1:19; preferably 1:3.

[0023] The hyaluronic acid is a natural high-molecular-weight linear polysaccharide formed by the repeated linkage of disaccharide units composed of D-glucuronic acid and N-acetylglucosamine, and the molecular weight of the hyaluronic acid is 100~400 kDa. The salt of the hyaluronic acid may include one or more of sodium salt, potassium salt, calcium salt, magnesium salt or zinc salt.

[0024] The aqueous phase may also contain lipophilic food nutrients such as curcumin, beta-carotene, lycopene, vitamin E, n-3 fatty acids, and vitamin A.

[0025] The oil phase may include, but is not limited to, soybean oil, corn oil, rapeseed oil, sunflower oil, palm oil, castor oil, conjugated linoleic acid, and linolenic acid.

[0026] The resulting high internal phase emulsion gel can be used to enhance the physicochemical stability of emulsions, for the protection and delivery of many active substances such as β-carotene, lutein, curcumin, etc., or as a fat substitute.

[0027] Beneficial effects of this invention: This invention prepares high-pressure homogenized functional materials—Pickerling particles with limited compliance—based on green physical modification technology. These soft particles with limited compliance are used as high-performance interface stabilizing particles (Pickerling particles) to produce materials such as emulsions, foams, emulsion gels, and high internal phase emulsion gels. These materials can also be applied to the creation of products in various fields such as food (e.g., mayonnaise and salad dressing), health products, cosmetics, personal care products, detergents, pharmaceuticals, and medicine.

[0028] This invention enables the one-step modification of natural casein micelle microgels through industrial-scale high-pressure homogenization to successfully obtain soft particles with limited compliance. The hierarchical casein micelle assemblies, upon exposure to high-energy shear and pressure, do not directly disintegrate but undergo plastic deformation, producing a "hard core-soft shell" structure with radially decreasing internal network cross-linking density. This core-shell structure combines the advantages of fully soft and hard particles, enabling rapid diffusion, adsorption, and strong anchoring at fluid interfaces, effectively reducing interfacial tension and resisting lateral compression. The preparation steps of this invention are very simple, reproducible, and suitable for industrial-scale production. Compared to chemical modification to obtain high-performance Pickering particles, this method avoids the use of chemical reagents, reducing environmental pollution during manufacturing and ensuring the soft particles can be used as food-grade particles, thus guaranteeing food safety.

[0029] The limited compliance soft particles prepared by this invention form an interlocking network at the fluid interface, exhibiting excellent foaming ability and emulsification stability. They can be used as high-performance and stable Pickering particles to encapsulate and deliver bioactive substances, gel liquid oils, and help solve the antioxidant problems of oils, and to prepare materials such as emulsions, foams, emulsion gels and high internal phase emulsion gels.

[0030] This invention utilizes Pickering particles with limited compliance to prepare high internal phase emulsion gels, adding hyaluronic acid and / or hyaluronic acid salts, and applies them to the preparation of foods such as salad dressings, mayonnaise, chocolate sauce, peanut butter, and walnut butter, which can reduce the amount of seasonings such as sugar or salt used in these foods. Attached Figure Description

[0031] Figure 1 SDS-PAGE spectra of MPC before and after HPH / HPM treatment (including untreated MPC, MPC treated with HPH 30~150MPa and MPC treated with HPM 30~150 MPa). Figure 1 a represents the non-reduced SDS-PAGE of the MPC dispersion before and after HPH treatment. Figure 1b represents the non-reduced SDS-PAGE of the MPC dispersion before and after HPM treatment. Figure 1 A, Figure 1 C represents the non-reduced SDS-PAGE and reduced SDS-PAGE of the ultracentrifuged supernatant of the MPC dispersion before and after HPH treatment. Figure 1 B. Figure 1 D represents the non-reduced SDS-PAGE and reduced SDS-PAGE of the ultracentrifuged supernatant of the MPC dispersion before and after HPM treatment.

[0032] Figure 2 The conformational and surface hydrophobicity changes of MPC before and after HPH / HPM treatment are shown in (A) circular dichroism, (B) endogenous fluorescence spectrum, and (C) surface hydrophobicity.

[0033] Figure 3 Representative TEM (A) and AFM (B) images of MPC dispersions before and after HPH / HPM treatment; Figure 4 The dynamic interfacial tensions of the MPC dispersions before and after HPH / HPM treatment are shown for the gas-water interface (A&B) and the oil-water interface (C&D).

[0034] Figure 5 Functional properties of MPC dispersions before and after HPH / HPM treatment: (A) Solubility, (B) Zeta potential, (C) Foaming ability, (D) Foam stability, (E) Emulsifying activity index, (F) Emulsifying stability index.

[0035] Figure 6 A high internal phase emulsion with an oil phase ratio of 75% was prepared from untreated aged MPC with a concentration of 1%–6% in 50 mL glass vials.

[0036] Figure 7 A high internal phase emulsion with an oil phase ratio of 75% was prepared in 50 mL glass vials for aged MPC with a concentration of 1%–6% after treatment at HPH 120 MPa.

[0037] Figure 8 A high internal phase emulsion with an oil phase ratio of 75% was prepared in 50 mL glass vials for aged MPC with a concentration of 1%–6% after HPM 90 MPa treatment.

[0038] Figure 9 CLSM diagram of a high internal phase emulsion with an oil phase ratio of 75% prepared from aged MPC with a concentration of 4% after HPH 120 MPa treatment in a 100 mL beaker.

[0039] Figure 10CLSM diagram of a high internal phase emulsion with an oil phase ratio of 75% prepared from aged MPC with a concentration of 6% after HPH 120 MPa treatment in a 100 mL beaker.

[0040] Figure 11 CLSM diagram of a high internal phase emulsion with an oil phase ratio of 75% prepared from aged MPC with a concentration of 4% after HPM 90 MPa treatment in a 100 mL beaker.

[0041] Figure 12 CLSM diagram of a high internal phase emulsion with an oil phase ratio of 75% prepared from 6% MPC after HPM 90 MPa treatment in a 100 mL beaker.

[0042] Figure 13 Storage stability of high internal phase emulsion gels prepared from untreated fresh MPC.

[0043] Figure 14 Storage stability of emulsion gels prepared from fresh MPC treated with HPH 120 MPa.

[0044] Figure 15 Centrifugal stability of emulsion gels prepared from fresh MPC before and after HPH 120 MPa treatment.

[0045] Figure 16 Inverted fluorescence images of emulsion gels prepared from fresh MPC before and after HPH 120 MPa treatment. Detailed Implementation

[0046] Methods for measuring indicators: SDS-PAGE analysis of modified MPC: SDS-PAGE analysis was performed on the unhomogenized MPC dispersion and the HPH / HPM-treated MPC solution to examine changes in protein composition after treatment. MPC (5% w / w) was diluted 25-fold with deionized water, and then diluted with SDS sample buffer at a ratio of 1:1 (v:v) before loading. Non-reducing SDS-PAGE was used to analyze the total MPC dispersion. The MPC dispersion was ultracentrifuged (100,000 rpm, 1 h, 20℃), and the protein concentration of the ultracentrifugation supernatant was diluted to ~2 mg / mL. Non-reducing and reducing SDS-PAGE were then performed. After preparing suitable gels (12% separating gel, 4% stacking gel), 15 μL of protein sample was injected into the sample wells. The gels were stained with Coomassie Brilliant Blue G-250 and photographed, then destained for 2–3 h until the background color was completely removed, and then scanned and photographed.

[0047] Structural characteristics analysis of modified MPC: The modified MPC obtained after HPH / HPM treatment in the examples was analyzed for its secondary and spatial structures using circular dichroism spectroscopy (CD) and intrinsic fluorescence spectroscopy to characterize the effect of high-pressure homogenization on the MPC structure. Samples before and after HPH / HPM treatment were centrifuged at 10,000 r / min for 20 min at 20 °C. The supernatant was filtered through a 1.6 μm GF / A filter membrane, and the filtrate was diluted to a protein concentration of 0.2 mg / mL (determined by the BCA method). The filtrate was injected into a 1 mm quartz cuvette, and the circular dichroism absorbance was measured in the far-UV region (190–260 nm) at room temperature and continuous nitrogen purging. The absorption rate was 50 nm / min, with spectral intervals of 1 nm, and the data were accumulated in three steps. After processing with Pro-Data Viewer, the relative content of secondary structures was calculated using CDNN software.

[0048] The intrinsic fluorescence of MPC before and after HPH / HPM treatment was measured using a spectrometer (Hitachi I, F-7000, China). The concentration of each sample was adjusted to 0.2 mg / mL with 0.01 M PBS (pH 7.0). The excitation wavelength was 280 nm, and emission spectra in the 300–450 nm range were collected in a constant slit of 5 nm.

[0049] Surface hydrophobicity analysis of modified MPC: Protein surface hydrophobicity (H0) was assessed using the fluorescent probe ANS (8 mM, 0.01 M phosphate buffer, pH 7.0). Protein concentrations ranged from 0.005% to 0.20% w / w. Fluorescence intensity of MPC solutions (unhomogenized MPC dispersions, HPH-treated MPC solutions, and HPM-treated MPC solutions diluted with phosphate buffer containing and without ANS to obtain MPC solutions with protein concentrations ranging from 0.005% to 0.20% w / w) was measured using an F-7000 fluorescence spectrometer. Excitation wavelength was 390 nm, emission wavelength was 470 nm, and slit width was 5 nm. The net fluorescence intensity (A) of each MPC solution was recorded. net It is calculated using the following formula: A net = A protein+ANS – A protein Where A protein+ANS and A protein The fluorescence intensities are shown for MPC solutions with and without ANS, respectively. A net vs The slope of the protein concentration (mg / mL) curve is H0.

[0050] Particle size, potential, pH and turbidity analysis of modified MPC: The refractive indices of the dispersion medium and the protein were 1.33 and 1.57, respectively. The particle size of the unequalized MPC dispersion and the HPH / HPM-treated MPC solution was measured using a Microtrac S3500 laser particle size analyzer (Microtrac Inc., Largo, FL, USA), with a detection range of 0.0107–2000 μm. The zeta potential of the unequalized MPC dispersion diluted 500 times with distilled water and the HPH / HPM-treated MPC solution was measured at 25 °C using a Zetasizer Nano ZS (Malvern Instrument Co., Ltd., UK) at 25 °C. The pH value of the samples was determined using a pH meter. The absorbance of the undiluted MPC dispersion was measured at 860 nm using a UV-Vis spectrophotometer (UV-1200, MAPADA Co., Ltd., Shanghai, China).

[0051] Transmission electron microscopy (TEM) analysis of modified MPC: TEM images of unhomogenized MPC, HPH (120 MPa), and HPM (90 MPa) treated MPC were observed using a Hitachi-7800 (Hitachi, Ltd., Tokyo, Japan). The MPC dispersion was mixed with 3% warm, low-temperature gelling agarose (Sigma-Aldrich, Shanghai, China) at a 1:1 ratio and then gelled at 4°C for 15 min. Samples were cut into small pieces (~ 1×1×1 mm). 3 Samples were stored in 0.1 M PBS buffer (pH 7.2) containing 2.5% w / w glutaraldehyde and fixed overnight at 4°C. Samples were fixed in 1% w / w osmium tetroxide solution for 2 h. Samples were then dehydrated for 15 min each in 30, 50, 70, 80, 90, and 95% ethanol solutions, followed by treatment with 100% ethanol for 20 min, and finally transposed to pure acetone for 20 min. Samples were treated with a mixture of Spurr embedding agent and acetone (v:v=1:1) for 1 h; then with a mixture of Spurr embedding agent and acetone (v:v=3:1) for 3 h; and finally treated overnight with pure embedding agent. Infiltrated samples were heated overnight at 70°C. Ultrathin sections were cut using a LEICA EM UC7 ultramicrotome to obtain sections with a diameter of 70–90 nm. The sections were stained with lead citrate solution and uranium acetate solution for 5–10 min each, and then observed under a transmission electron microscope.

[0052] Atomic force microscopy (AFM) analysis of modified MPC: Unhomogenized MPC dispersions, HPH (120 MPa) treated MPC solutions, and HPM (90 MPa) treated MPC solutions (1 μg / mL) were dropped onto the silicon wafer surface, immediately flash-frozen in liquid nitrogen, and then freeze-dried. Morphology and particle height were observed and measured at room temperature using a MuLtimode 8 atomic force microscope (Bruker Corporation, Karlsruhe, Germany). Imaging parameters were automatically optimized using ScanAsyst Mode, with a linear scan rate optimized to 1 Hz, a scan angle of 0.00°, and a scan resolution of 512 samples per line. Images were analyzed using NanoScope Analysis software (Version 1.40, Bruker Corporation, Karlsruhe, Germany).

[0053] Dynamic interfacial tension analysis of modified MPC: The surface tension (0.1% w / w) of unhomogenized MPC dispersions and HPH / HPM-treated MPC solutions at gas-water and oil-water interfaces was measured using a video optical contact angle meter (OCA15EC, Dataphysics, Germany) with pendant drop technique. The surface tension (γ) at 20°C was obtained by fitting the droplet profile to the Young-Laplace capillary equation. The microsyringe used in the experiment had an outer diameter of 1.65 mm, and the injection rate was kept as slow as possible to ensure the accuracy of the injection volume. The cleanliness of the system was checked before measurement; the surface pressure of pure water should be less than 0.3 mN / m.

[0054] Solubility analysis of modified MPC: The unhomogenized MPC dispersion and the HPH / HPM-treated MPC solution were centrifuged at 20°C and 700 g for 10 min. The resulting supernatant was filtered through a membrane (GF / A Microfiber filter paper, 1.6 μm pore size, Whatman). 5 g of both the MPC dispersion and the supernatant were weighed into pre-weighed weighing dishes and placed in an oven at 105°C for 12 h until constant weight was achieved. After cooling in a desiccator for approximately 30 min, the samples were weighed. The solubility (%) of the MPC powder was expressed as the ratio of solids content in the supernatant to that in the total dispersion.

[0055] Analysis of the foaming ability (FA) and foaming stability (FS) of modified MPC: Take 50 mL of the unhomogenized MPC dispersion and the HPH / HPM treated MPC solution (5% w / w) into beakers respectively, and disperse them at 10000 r / min for 2 min using a high-speed shear disperser (T18 Ultra Turrax, IKA, Wilmington, US). Then, gently and quickly pour the samples from the beakers completely into a 250 mL graduated cylinder and measure V2 and V3. After standing for 30 min, measure V4 and V5. The foaming capacity FA (%) and foam stability FS (%) of MPC can be calculated using the following two formulas respectively: FA (%) = [(V3-V2) / V c ] ×100% FS (%) = [(V5-V4) / (V3-V2)] ×100% Note: V c =50 mL, V2 is the volume of the lower aqueous phase, V3 is the total volume of the aqueous phase and foam, V4 is the volume of the lower aqueous phase after standing for 30 min, and V5 is the total volume of the aqueous phase and foam after standing for 30 min.

[0056] Analysis of the emulsifying activity index (EAI) and emulsifying stability index (ESI) of modified MPC: 40 mL of unhomogenized MPC dispersion, HPH / HPM treated MPC solution (1% w / w), and 10 mL of soybean oil were mixed and homogenized for 3 min at a shear rate of 10000 r / min using an IKA T18 high-speed shear disperser (Germany). After standing for 0 min and 30 min respectively, 50 μL of the emulsion was taken from 1 cm below the bottom of the beaker and dispersed in 8 mL of 0.1% w / v SDS solution. After vortexing, the absorbance at 500 nm was measured using a UV-1200 ultraviolet spectrophotometer. EAI and ESI values ​​were calculated using the following formulas: EAI (m 2 / g) =(2×2.303×A0×D) / (C×f×φ×10 4 ) ESI (min) = [A0 / (A0-A 30 )]×30 Where D is the dilution factor, C is the initial protein concentration (g / mL) before emulsion preparation, f is the optical path length (1 cm), φ is the oil phase volume (0.2), and A0 and A 30 The absorbance values ​​are at 0 and 30 min, respectively.

[0057] Microstructure determination of modified MPC Pickering high internal phase emulsion gel—laser confocal microscopy (CLSM): The specific distribution of MPC and oil in the fresh emulsion gel of Example 3 was observed using a laser confocal microscope. The oil phase was stained with the fluorescent dye Nile Red, and the MPC was stained with Nile Blue. Nile Blue (0.1% w / w) and Nile Red (0.1% w / w) solutions were prepared using 1,3-propanediol to reduce the influence of organic solvents on the oil phase during staining. Before preparing the emulsion gel, 30 mL of MPC dispersion was placed in a 100 mL beaker, and 30 μL of Nile Blue staining solution was added. 10 mL of conjugated linoleic acid was placed in a 50 mL centrifuge tube, and 10 μL of Nile Red staining solution was added. Then, the stained MPC dispersion and CLA were dispersed by high-speed shearing to prepare the stained emulsion gel. 10 μL of the emulsion gel was placed on a glass slide, covered with a coverslip, and observed under a laser confocal microscope. The excitation wavelengths for Nile Blue and Nile Red were 633 nm and 488 nm, respectively.

[0058] In the following examples, a high-pressure homogenizer (Nano Disperser, ATS Engineering Limited Co., Ltd, Canada) was used for homogenization, which can perform ordinary high-pressure homogenization (HPH) or microfluidic high-pressure homogenization (HPM).

[0059] Example 1: Preparation of Functional Materials Based on MPC In this embodiment, aged MPC powder is used as raw material, and the MPC dispersion is treated by HPH / HPM to obtain emulsifier-Picklerin particles.

[0060] The specific process is as follows: Aged MPC powder was dispersed in ultrapure water and gently stirred at 600 rpm for 2 h at room temperature, followed by gentle stirring at 600 rpm for 10 h at 15°C. After complete hydration, a concentration of 50 g·L⁻¹ was prepared. -1 A dispersion of (5% w / w).

[0061] The dispersion was first preheated to 50°C, and then subjected to conventional high-pressure homogenization (HPH) or micro-jet high-pressure homogenization (HPM) using a high-pressure homogenizer (Nano Disperser, ATSEngineering Limited Co., Ltd, Canada). The homogenization pressures were 30, 60, 90, 120 or 150 MPa, and the homogenization was performed three times to obtain the MPC solution.

[0062] Characterization analysis of the obtained emulsifier: 1. The changes of each protein component in MPC dispersion / solution and ultracentrifugation supernatant before and after HPH / HPM treatment were investigated by SDS-PAGE. In the untreated MPC dispersion, SDS-PAGE ( Figure 1 (ab) showed that the main components were α-casein and β-casein, followed by β-Lg and α-La. We also observed disulfide-linked aggregates and low-abundance protein components in whey protein. After homogenization, the position and intensity of the protein bands did not change significantly, indicating that homogenization does not alter the molecular weight of the protein. Homogenization may affect the micelles themselves, leading to changes in the composition and content of soluble proteins in the solution; therefore, further electrophoretic analysis of the ultracentrifuged supernatant was performed, such as... Figure 1 As shown in A-D, the soluble proteins in untreated MPC mainly consist of β-Lg and α-La, followed by β-casein, and a small number of small protein aggregates. After homogenization, the main types of soluble proteins remained unchanged, but with increasing pressure, the content of casein, especially α-casein and β-casein, continuously increased. This suggests that high-pressure homogenization may have disrupted the stability of casein micelles, causing some casein to migrate out of the micelles. In non-reducing electrophoresis, no aggregates were found in the sample inlet of the corresponding lane of untreated MPC. However, with increasing pressure, especially at 90-150 MPa, we observed the appearance of aggregates, which disappeared in reducing electrophoresis, and the bands of BSA and β-Lg were significantly enhanced. This indicates that homogenization may induce thiol / disulfide interactions in proteins to form new protein complexes.

[0063] 2. Secondary structure changes in MPC induced by HPH / HPM treatment were detected using CD spectroscopy measured in the far-UV region. Untreated MPC exhibited a wide range of negative ellipticity between 200 and 225 nm, including random coils, β-sheets, and α-helixes. In addition to casein (~83% w / w), MPC also contained approximately 17% w / w whey protein. WPI exhibited a wide range of negative ellipticity between 210 and 220 nm. Compared to the control group, the increased negative ellipticity of MPC-HPH and MPC-HPM between 200 and 225 nm indicated that homogenization treatment altered the protein's secondary structure. Particularly around 200 nm, the significantly increased negative ellipticity indicated increased conformational disorder after homogenization.

[0064] 3. The spatial structure changes of MPC caused by HPH / HPM treatment were analyzed using intrinsic fluorescence spectroscopy by detecting the maximum absorption wavelength (λ) of the protein molecules. max ) and intrinsic fluorescence intensity (I f To judge by the changes in () Figure 2B). Unprocessed MPC λ max The wavelength is 340.8 nm, and after homogenization, λ max A slight blue shift (~2 nm) occurred, and If was significantly enhanced. λ max and I f The fluctuations indicate that the spatial structure of the MPCs changed during processing. The loss of κ-casein on the surface of the micelles after homogenization and the denaturation of whey protein inevitably lead to the exposure of more Trp residues, thereby increasing fluorescence intensity.

[0065] 4. The change in the number of hydrophobic groups / residues on the surface of MPC after HPH / HPM treatment can be determined by surface hydrophobicity (H0). For example... Figure 2 As shown in Figure C, the H0 of untreated MPC was 175.75 mL / mg. After HPH / HPM treatment, H0 significantly increased and showed a positive correlation with pressure. Specifically, after treatment with 150 MPa pressure, H0 increased to 210.34 mL / mg (HPH) or 236.39 mL / mg (HPM), indicating that high pressure disrupted the hydrophobic interactions between protein molecules, thereby exposing hydrophobic groups hidden within the aggregates. This is consistent with the effect of homogenization on I... f The results showed a significant increase (Figure 2A). As a high-energy processing method, HPM can exert strong shear force on materials and generate high-speed jets, thereby causing the particles to be highly fragmented. More hydrophobic groups are exposed on the surface of protein molecules, effectively enhancing the H0 of MPC, and the effect is more obvious than that of HPH treatment.

[0066] 5. The particle size, pH, and turbidity of the MPC dispersion before and after HPH / HPM treatment are shown in Table 1. After HPH / HPM treatment, the average particle size decreased significantly and the particle size distribution narrowed. This is because homogenization disrupts the hydrophobic interactions between micelles, causing the insoluble aggregates to dissociate. When the homogenization pressure reaches 120 MPa at HPH or 90 MPa at HPM, the particle size gradually increases, indicating the presence of aggregation. One reason for the high-pressure-induced increase in the particle size of the MPC dispersion may be the recombination of partially dissociated casein micelles and the formation of micellar aggregates. Another reason may be the interaction between denatured β-Lg and casein micelles to form aggregates. The change in turbidity of the MPC dispersion caused by homogenization treatment is consistent with the change in particle size. The pH of the dispersion did not change significantly before and after treatment. As a higher-energy processing method, HPM-treated samples exhibit smaller particles and a narrower particle size distribution. This is likely because the dispersion generates a high-speed jet within the microfluidic diamond interaction cavity, subjected to intense shearing, cavitation, and impact forces, which more thoroughly disrupts micelles and their aggregates, resulting in more protein fragments. However, because HPM treatment exposes more internal hydrophobic groups, more micelles will re-aggregate through hydrophobic interactions, thus forming larger particles.

[0067] Table 1

[0068] 6. Morphological characteristics of MPC before and after HPH / HPM treatment were determined by TEM ( Figure 3 A) and AFM ( Figure 3 B) To observe. For example Figure 3 As shown in Figure A, after high-pressure homogenization, the originally strongly aggregated and rough-surfaced casein micelles transformed into dispersed and smoother individual micelles. They also exhibited a distinct inner-outer structure with significant contrast, densely packed at the center and loosely packed at the periphery, resembling a "fried egg" shape. This indicates that the mechanical energy of pressure and shear force acted on the micelles from the outside in along the micelle radius, causing the κ-casein layer on the micelle surface to detach and partially disrupting the interactions between proteins within the micelles. Besides the dissociation of some smaller casein submicelles, most proteins maintained partial interactions without dissociation, forming a lower-contrast outer layer of the micelles; proteins closer to the inner part of the micelles were likely subjected to weaker effects, maintaining their original structure and appearing as higher-contrast intermediate particles. Furthermore, Figure 3B shows that the micelle nanoparticles exhibit a morphology with a relatively high center (approximately 20-25 nm) and almost no height at the periphery, i.e., a tightly packed center and a loose, flexible outer layer. Compared to micelles in untreated MPC, this structure is less rigid, which may affect its macroscopic material properties. Comparing the effects of the two treatment methods, it is easy to see that adhesion between casein micelles still exists in the dispersion treated with HPH, while HPM treatment, as a higher-energy processing method, forms more, smaller, and more discrete casein micelles. Figure 3 AFM images of B show that the homogenized micelles exhibit a morphology with a relatively high center (approximately 20–25 nm) and almost no height at the periphery, indicating that the micelles are tightly compacted in the center and loosely flexible on the outer layer. This further confirms the TEM (emergence spectroscopy) results. Figure 3 The homogenized "fried egg" structure observed in Ab2 & Ab3. Compared to micelles in untreated MPC, this structure is less rigid, which may affect its macroscopic material properties. Figure 3 As shown in Bb2 & Bc2, similar to TEM observations, the higher-energy HPM exerted a stronger destructive force on casein micelles. Compared to HPH-MPC (diameter 200–800 nm), HPM-MPC exhibits a large number of smaller and more dispersed casein micelles (diameter 20–70 nm), with lower particle height and greater uniformity. Figure 3 Bb3 & Bc3 form a looser, softer "fried egg" structure with less rigidity.

[0069] 7. The diffusion, adsorption, and rearrangement behavior of MPC at the fluid interface was investigated by measuring the dynamic surface tension of the fluid interface. Figure 4 The results showed that the smaller nanoparticles after homogenization could diffuse to the air-water interface more quickly and effectively reduce the interfacial tension. After 1800 s of equilibration, the MPCs with the best surface activity were those treated with HPH 120 MPa and HPM 90 MPa, with the interfacial tension decreasing from 50.93 mN / m to 47.93 mN / m and 43.8 mN / m, respectively. The final values ​​of the oil-water interfacial tension of the MPCs before and after treatment were similar, indicating that the density of adsorbable particles was sufficient to saturate the interface.

[0070] 8. Figure 5 A shows that HPH / HPM treatment can significantly improve the solubility of MPC, from 45.51% (untreated MPC) to nearly 100%. Figure 5 B indicates that the absolute value of the zeta potential of MPC increases after HPH / HPM treatment, rising from -19.614 mV (untreated MPC) to -23 mV ~ +26 mV. Figure 5C&D results show that HPH / HPM treatment can significantly improve the foaming ability of MPC, increasing it from 105.33% (untreated MPC) to 201.20% (HPH 120 MPa treated MPC) and 199.85% (HPM 90 MPa treated MPC), respectively. This is related to the appearance of "fried egg" shaped soft particles with higher surface activity and network crosslinking density gradient after treatment. After 30 min of foam formation, the foam volume retention rate of the untreated MPC dispersion was 71.62±2.52%. However, all HPH treatment pressure groups negatively affected the stability of MPC foam formation, especially at 30~90 MPa, where the FS decreased by about ~50%. In contrast to the HPH treatment, high-pressure homogenization treatment at 60 MPa and above helped improve the ability of MPC to stabilize foam, with FS of 78.44±4.89% (60 MPa) and 73.91±2.59% (90 MPa), respectively. This may be related to the increase in the viscoelasticity of the interfacial film or the large accumulation of colloidal particles in the continuous phase, which can more effectively prevent foam coarsening or even agglomeration, ultimately achieving better foam stability. Figure 5 E&F results showed that the emulsifying activity index (EAI) of untreated MPC was 34.06 ± 0.14 m. 2 / g, after HPH treatment, EAI became 33~34 m 2 / g indicates that HPH cannot significantly improve emulsifying activity; however, after HPM treatment, EAI increased to 37-39 m. 2 / g showed a certain degree of improvement. In addition, HPH / HPM can significantly improve emulsion stability, with the best improvement effect being 71.78±5.77 min for HPH treatment at 120 MPa and 74.26±15.61 min for HPM treatment at 90 MPa, thus achieving more durable emulsion stability.

[0071] Example 2: Application of functional materials prepared based on aged MPC as emulsifiers in the preparation of Pickering high internal phase emulsion gels Aged MPC powder was dispersed in ultrapure water and gently stirred at 600 rpm for 2 h at room temperature, followed by gentle stirring at 600 rpm for 10 h at 15°C. After thorough hydration, an MPC dispersion with a concentration of 12% w / w was prepared. The dispersion was preheated to 50°C and then subjected to either HPH treatment (homogenization pressure of 120 MPa) using a high-pressure homogenizer or HPM treatment (homogenization pressure of 90 MPa) using a microfluidic high-pressure homogenizer. Both homogenization treatments were performed three times to obtain an MPC solution, i.e., Pickering particles with limited compliance.

[0072] Next, water was added to dilute the untreated MPC dispersion, the HPH-treated MPC solution, and the HPM-treated MPC solution to concentrations of 1%, 2%, 3%, 4%, 5%, and 6% (w / w), respectively. 5 mL of the untreated MPC dispersion or either of the two homogenized MPC solutions was placed in a 50 mL glass vial, and 20 mL of CLA was placed in a 25 mL glass graduated cylinder. The CLA was slowly added to the MPC dispersion / solution using a constant flow pump, while simultaneously undergoing high-speed shear dispersion in the 50 mL glass vial to prepare a Pickering high internal phase emulsion gel.

[0073] Conjugated linoleic acid (CLA) is a functional oil rich in unsaturated fatty acids, but its direct addition to food can negatively impact the product's flavor and texture, thus affecting its taste. Free CLA is difficult to distribute evenly in food, leading to poor product stability. Furthermore, unsaturated fatty acids contain numerous double bonds, making them extremely sensitive to light, heat, and oxygen. When added to food, they are prone to oxidation, producing unpleasant odors, reducing product quality and shelf life, and hindering large-scale and commercial applications. This embodiment uses high-pressure homogenization modified MPC and unmodified MPC to prepare CLA high-internal-phase emulsion gels, respectively, to investigate the effect of homogenization pretreatment on the properties of the emulsion gels prepared from MPC. This also improves the application defects of CLA due to its susceptibility to oxidation, expanding its application forms and fields.

[0074] Pickering high internal phase emulsion gel preparation is as follows: Aged MPC powder was dispersed in ultrapure water and gently stirred at 600 rpm for 2 h at room temperature, followed by gentle stirring at 600 rpm for 10 h at 15°C to achieve full hydration and prepare a 12% w / w MPC concentration. The dispersion was preheated to 50°C and then subjected to HPH treatment (homogenization pressure 120 MPa) or HPM treatment (homogenization pressure 90 MPa) using a microfluidic high-pressure homogenizer. Both homogenization treatments were performed three times. The solutions were then diluted with water to concentrations of 1%, 2%, 3%, 4%, 5%, and 6% (w / w), respectively. 5 mL of untreated MPC dispersion or either of the two homogenized MPC solutions was placed in a 50 mL glass vial, and 20 mL of CLA was placed in a 25 mL glass graduated cylinder. CLA was slowly added to the MPC dispersion / solution using a constant flow pump while simultaneously undergoing high-speed shear dispersion to prepare a high internal phase emulsion gel.

[0075] Performance analysis of the obtained high internal phase emulsion gel: The freshly prepared emulsion gel was placed in a room temperature (25°C) environment, and its macroscopic state was recorded by taking pictures. Figure 6From left to right, the MPC concentrations (the ratio of MPC powder mass to the total mass of the MPC solution) are 1%, 2%, 3%, 4%, 5%, and 6% w / w, respectively, with an oil phase volume ratio of 80% (referring to the ratio of the oil phase volume used to prepare the emulsion gel to the total oil-water phase volume). The results show that MPC dispersions with different protein concentrations that have not undergone high-pressure homogenization cannot produce high-internal-phase emulsions. Figure 7 From left to right, these represent MPC concentrations of 1%, 2%, 3%, 4%, 6%, and 5% w / w, with an oil phase volume ratio of 80%. The results show that high internal phase emulsion gels with an oil phase ratio of 80% can be prepared by high-pressure homogenization with 3%, 4%, and 6% MPC. Figure 8 From left to right, the MPC concentrations are 1%, 2%, 3%, 4%, 5%, and 6% w / w, with an oil phase volume ratio of 80%. The results show that both 2% and 3% MPC treatments can prepare high internal phase emulsion gels with an oil phase ratio of 80%.

[0076] Example 3: Application of functional materials prepared based on aged MPC as emulsifiers in the preparation of Pickering high internal phase emulsion gels Pickering high internal phase emulsion gel was prepared in a 100 mL plastic beaker using unsaturated fatty acid-conjugated linoleic acid (CLA) as the oil phase and MPC solution treated with HPH 120 MPa or HPM 90 MPa as the aqueous phase.

[0077] Pickering high internal phase emulsion gel preparation is as follows: In this embodiment, conjugated linoleic acid high internal phase emulsion gels were prepared by using MPC modified by high pressure homogenization or MPC modified by microfluidic treatment.

[0078] Aged MPC powder was dispersed in ultrapure water and stirred at 600 rpm for 2 h at room temperature, followed by stirring at 600 rpm for 10 h at 15 °C to fully hydrate the MPC powder to a concentration of 12% w / w. The dispersion was preheated to 50 °C and then subjected to either HPH treatment (homogenization pressure 120 MPa) or HPM treatment (homogenization pressure 90 MPa) using a high-pressure homogenizer, with each homogenized sample being homogenized three times. The resulting solutions were then diluted with water to concentrations of 4% and 6% (w / w). 10 mL of the MPC dispersion / solution was placed in a 100 mL plastic beaker, and 30 mL of CLA was placed in a 50 mL centrifuge tube. The CLA was slowly added to the MPC dispersion / solution using a constant flow pump while simultaneously undergoing high-speed shear dispersion to prepare a high internal phase emulsion gel.

[0079] Performance analysis of the obtained high internal phase emulsion gel: The distribution and state of proteins and CLA in the prepared high internal phase emulsion gel were observed using laser confocal microscopy (CLSM). The stained samples were observed under a laser confocal microscope with excitation wavelengths of 638 nm and 488 nm for Nile blue and Nile red, respectively. Figures 9-12 This indicates that the microstructure of the gel formation varies with the pretreatment method and concentration of MPC. Both pretreatment methods enable the preparation of high internal phase emulsion gels with MPC, characterized by tightly packed oil droplets with a surface stabilized by protein particles, and the oil droplets exhibiting an irregular hexagonal morphology. Figure 9 As can be seen from section 10, after treatment with HPH120 MPa, the oil droplet size distribution of the MPC dispersion prepared with 4% MPC was more uniform than that of the emulsion gel prepared with 6% MPC. From... Figure 11 As shown in Figure 12, after treatment with HPM 90 MPa, the oil droplet size distribution of the MPC dispersion prepared with 6% MPC was smaller and more uniform than that of the emulsion gel prepared with 4% MPC. Simultaneously, a large number of protein particles were adsorbed onto the oil droplet surface, forming a highly ordered network bound to the oil droplets, thus maintaining relative stability within the system. Furthermore, a large number of protein particles remained unadsorbed on the oil droplet surface; these unadsorbed proteins cross-linked to provide a steric barrier, preventing oil droplet aggregation and contributing to the longer-term stability of the emulsion gel.

[0080] Example 4: Application of functional materials prepared based on fresh MPC as emulsifiers in the preparation of high internal phase emulsion gels Pickering high internal phase emulsion gels were prepared in 50 mL glass vials using soybean oil as the oil phase and untreated MPC solution or MPC solution treated with pH 120 MPa as the aqueous phase.

[0081] Pickering high internal phase emulsion gel preparation is as follows: Fresh MPC powder was dispersed in ultrapure water to obtain a 5% w / w MPC solution. Then, the solution was homogenized three times at HPH 120 MPa using a high-pressure homogenizer. 5 mL of the MPC dispersion / solution was placed in a 50 mL glass vial, and 15 mL of soybean oil was placed in a 25 mL glass graduated cylinder. The soybean oil was added to the MPC dispersion / solution using a constant flow pump while simultaneously undergoing high-speed shear dispersion to prepare a high internal phase emulsion gel.

[0082] Performance analysis of the obtained high internal phase emulsion gel: 1) Storage stability analysis of emulsion gels prepared from fresh MPC before and after HPH treatment: Freshly prepared emulsion gels were photographed after being left to stand for a period of time (0, 24, 48, 72, 96, 120, and 144 h) to observe their storage stability. Figure 13 &14 showed that no unstable stratification occurred after 72 h of storage of the emulsion gel, but pores appeared on the cup wall. The MPC emulsion gel without high-pressure homogenization showed more pores of varying shapes and sizes, while the MPC emulsion gel treated with HPH 120 MPa showed many tiny pores. After 96 h of storage, the number of pores in the emulsion gel further increased.

[0083] 2) Centrifugal stability analysis of emulsion gels prepared from fresh MPC before and after HPH treatment: The prepared fresh emulsion gel was transferred into a centrifuge tube and centrifuged at 3000 g at 4 °C for 20 min. The centrifugal stability of the emulsion gel during storage (0, 24, 48, 96, 120 and 144 h) was observed. Figure 15 This indicates that both the untreated and HPH 120 MPa-treated MPC emulsion gels exhibited a lower protein solution layer after centrifugation. After 24 hours of standing, no oil phase precipitation was observed in any sample, and the bottom stratification disappeared. Furthermore, the untreated MPC emulsion gel almost completely collapsed, while the HPH 120 MPa-treated MPC emulsion gel sank but did not collapse. After standing for 48–96 hours, both types of gel samples continued to sink. After 120 hours of standing, the stratification of both gel samples disappeared, and sinking occurred.

[0084] 3) Inverted fluorescence image analysis of emulsion gels prepared from fresh MPC before and after HPH treatment: The distribution and state of oil droplets in the prepared fresh emulsion gel were observed using an inverted fluorescence microscope. Figure 16 This indicates that the oil droplets in the emulsion gel prepared from untreated MPC are of varying sizes, with some being quite large; while the oil droplets in the emulsion gel prepared from MPC treated with HPH120 MPa are smaller, more uniform in size distribution, and more densely packed.

[0085] Example 5: Application of functional materials prepared based on fresh MPC as emulsifiers in the preparation of sugar-reduced high internal phase emulsion gels To enrich the flavor of gel emulsions, various sweet flavoring substances, such as honey and jam, can be added to the aqueous phase; and hyaluronic acid can be added to enhance taste perception, thereby reducing the amount of sugary flavoring substances that need to be added.

[0086] Pickering high internal phase emulsion gel was prepared in a 500 mL plastic cup using walnut oil as the oil phase and MPC dispersion / solution (with added sodium hyaluronate and sugar-containing flavoring substances) before and after treatment at HPH 120 MPa as the aqueous phase.

[0087] Pickering high internal phase emulsion gel preparation is as follows: Fresh MPC powder was dispersed in a sugar solution of sodium hyaluronate (molecular weight 100 kDa) and completely hydrated to prepare an MPC-HA solution with a protein concentration of 5% (HA concentration 0.2% w / w). Then, the solution was homogenized three times at HPH 120 MPa using a high-pressure homogenizer. 150 mL of walnut oil was slowly added to 50 mL of the MPC-HA sugar solution using a constant flow pump, while simultaneously undergoing high-speed shear dispersion to prepare a high internal phase emulsion gel.

[0088] Sensory analysis of the obtained sugar-reduced high internal phase emulsion gel: Fifteen sensory evaluators were selected to taste the samples and compare them with sample A. They then selected the sample from B and C that they considered to be closest to sample A.

[0089] Sample A was prepared by adding 1 g / 100 mL of white granulated sugar to the aqueous phase. Sample B was prepared by adding hyaluronic acid with a 25% reduction in sugar content (i.e., 0.75 g / 100 mL) and 0.2% w / w 100 kDa to the aqueous phase. For sample C, when adding the S4 protein gel sample obtained in Example 2, a sugar content reduced by 50% (i.e., 0.5 g / 100 mL) and 0.2% w / w 100 kDa hyaluronic acid were added.

[0090] The three sample names were represented by three random numbers and presented to each consumer in a random order. Consumers independently evaluated the three samples by smelling and tasting them, testing their preference for the aroma, taste, and overall flavor using a 9-point preference scale (1 indicates strong dislike, and 9 indicates strong liking).

[0091] Questionnaire: Now please taste the sample. Take a small sip, spit it out, and then score it according to the prompts: (1) Please select the sample whose sweetness value is similar to that of sample xxx: (2) Product preference: I really dislike it, I dislike it quite a bit, I dislike it a little, I can't really say whether I like it or not, I like it a little, I like it quite a bit, I like it a lot, I like it extremely much.

[0092]

[0093] Based on preference ratings, 9 people felt that sample C had the same sweetness as sample A, indicating that adding 0.2% w / w 100 kDa hyaluronic acid can reduce sugar intake by 50%.

[0094] Example 6: Application of functional materials prepared based on fresh MPC as emulsifiers in the preparation of low-salt, high-internal-phase emulsion gels To enrich the flavor of protein gels, various savory flavorings, such as salt and soy sauce, can be added; and hyaluronic acid can be added to enhance taste perception, thereby reducing the amount of salt that needs to be added.

[0095] Pickering high internal phase emulsion gel was prepared in a 500 mL plastic cup using walnut oil as the oil phase and MPC dispersion / solution (with added sodium hyaluronate and sugar-containing flavoring substances) before and after treatment at HPH 120 MPa as the aqueous phase.

[0096] Pickering high internal phase emulsion gel preparation is as follows: Fresh MPC powder was dispersed in an aqueous solution of sodium hyaluronate (molecular weight 100 kDa) and completely hydrated to prepare an MPC-HA solution with a protein concentration of 5% (HA concentration 0.2% w / w). Then, the solution was homogenized three times at HPH 120 MPa using a high-pressure homogenizer. 150 mL of walnut oil was slowly added to 50 mL of the MPC-HA sugar solution using a constant flow pump, while simultaneously undergoing high-speed shear dispersion to prepare a high internal phase emulsion gel.

[0097] Sensory analysis of the obtained low-salt, high-internal-phase emulsion gel: Fifteen sensory evaluators were selected to taste the samples and compare them with sample A. They then selected the sample from B and C that they considered to be closest to sample A.

[0098] Sample A was prepared by adding 0.5 g / 100 mL of salt to the aqueous phase. Sample B was prepared by adding 25% less salt and 0.2% w / w 100 kDa hyaluronic acid to the aqueous phase. Sample C was prepared by adding 50% less salt and 0.2% w / w 100 kDa hyaluronic acid to the S4 protein gel sample obtained in Example 2.

[0099] The three sample names were represented by three random numbers and presented to each consumer in a random order. Consumers independently evaluated the three samples by smelling and tasting them, testing their preference for the aroma, taste, and overall flavor using a 9-point preference scale (1 indicates strong dislike, and 9 indicates strong liking).

[0100] Questionnaire: Now please taste the sample. Take a small sip, spit it out, and then score it according to the prompts. (1) Please select the sample whose salinity value is similar to that of sample xxx: (2) Product preference: I really dislike it, I dislike it quite a bit, I dislike it a little, I can't really say whether I like it or not, I like it a little, I like it quite a bit, I like it a lot, I like it extremely much.

[0101]

[0102] Based on preference ratings, 12 people felt that the saltiness of sample B was the same as that of sample A. This indicates that adding 0.2% w / w 100 kDa hyaluronic acid can reduce salt intake by 25%.

Claims

1. A method for preparing Pickering particles, characterized in that, The Pickering particles have limited compliance. By processing the milk protein dispersion using homogenization technology, Pickering particles with limited compliance can be obtained. The milk protein dispersion is an aqueous solution of milk protein, with a milk protein mass fraction of 1-12% w / w relative to water. The homogenization process involves stirring the milk protein dispersion at 200-800 rpm for 2 hours at 20-50°C, then stirring at 200-800 rpm for 10-12 hours at 10-15°C, followed by preheating at 50-70°C for 10-30 minutes, and finally performing either conventional high-pressure homogenization or microfluidic high-pressure homogenization. The conventional high-pressure homogenization uses a pressure of 120 MPa, while the microfluidic high-pressure homogenization uses a pressure of 90 MPa, with homogenization repeated 2-8 times.

2. The method for preparing Pickering particles according to claim 1, characterized in that, The milk protein is derived from cow's milk, goat's milk, sheep's milk, dromedary camel milk, Bactrian camel milk, donkey milk, or roe deer milk.

3. The method for preparing Pickering particles according to claim 2, characterized in that, The milk protein is liquid milk or milk protein powder.

4. The method for preparing Pickering particles according to claim 1, characterized in that, The milk protein is casein micelle powder, milk protein concentrate powder, skim milk powder, low-fat milk powder, or whole milk powder.

5. Pickering particles obtained by the method according to any one of claims 1 to 4.

6. The use of the Pickering particles according to claim 5, characterized in that, The uses include: for preparing emulsions and for preparing foams.

7. A high internal phase emulsion gel prepared using Pickering particles as described in claim 5, characterized in that, The high internal phase emulsion gel is obtained by high-speed shear dispersion using Pickering particles as described in claim 5 as the aqueous phase and at least one of soybean oil, corn oil, rapeseed oil, sunflower seed oil, palm oil, castor oil, conjugated linoleic acid, or linolenic acid as the oil phase.

8. The high internal phase emulsion gel according to claim 7, characterized in that, The aqueous phase also contains hyaluronic acid and / or hyaluronic acid salts.

9. The high internal phase emulsion gel according to claim 7 or 8, characterized in that, The hyaluronic acid has a molecular weight of 100-400 kDa, and the salt of the hyaluronic acid includes one or more of sodium, potassium, calcium, magnesium, or zinc salts.

10. The high internal phase emulsion gel according to claim 7 or 8, characterized in that, The aqueous phase also contains at least one of curcumin, beta-carotene, lycopene, vitamin E, n-3 fatty acids, and vitamin A.

11. Use of the high internal phase emulsion gel according to any one of claims 7-10, characterized in that, Used in the manufacture of food or daily chemical products.

Citation Information

Patent Citations

  • Casein gel particle emulsifier, and preparation method and use thereof

    CN106937737A